1998
DOI: 10.1038/bjc.1998.24
|View full text |Cite|
|
Sign up to set email alerts
|

Phase I study on docetaxel and ifosfamide in patients with advanced solid tumours

Abstract: Summary Docetaxel and ifosfamide have shown significant activity against a variety of solid tumours. This prompted a phase I trial on the combination of these drugs. This phase I study was performed to assess the feasibility of the combination, to determine the maximum tolerated dose (MTD) and the side effects, and to propose a safe schedule for further phase 11 studies. A total of 34 patients with a histologically confirmed solid tumour, who were not pretreated with taxanes or ifosfamide and who had received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…The MTD occurred at docetaxel 85 mg/m 2 and ifosfamide 5000 mg/m 2 , and the authors recommended that docetaxel be given prior to ifosfamide. In contrast to our study, there were no episodes of ifosfamide encephalopathy noted, and greater than 50% incidence of mild peripheral neuropathy, possibly due to a higher cumulative dose of docetaxel delivered (Pronk et al, 1998). It is difficult to compare different schedules of ifosfamide for relative efficacy or toxicity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The MTD occurred at docetaxel 85 mg/m 2 and ifosfamide 5000 mg/m 2 , and the authors recommended that docetaxel be given prior to ifosfamide. In contrast to our study, there were no episodes of ifosfamide encephalopathy noted, and greater than 50% incidence of mild peripheral neuropathy, possibly due to a higher cumulative dose of docetaxel delivered (Pronk et al, 1998). It is difficult to compare different schedules of ifosfamide for relative efficacy or toxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…In a previous phase I study of this combination, Pronk et al escalated the dose of both agents, and ifosfamide was infused over a 24-h period on day 1 only (Pronk et al, 1998). In addition they addressed the issue of scheduling, with docetaxel administered prior to ifosfamide in the first phase of the study, and reversal of the order of administration in the second part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as grade 4 neutropenia and febrile neutropenia represented the only significant toxicities in our study, the 10% incidence of the latter appears rather low and compares favorably to that of single agent docetaxel at 100 mg/m 2 with G-CSF support. The phase I study of Pronk et al [12], that has evaluated the feasibility of the docetaxel-ifosfamide combination without G-CSF in pretreated patients with a variety of advanced solid tumors determined the DLT of the combination being mainly neutropenia at docetaxel 85 mg/m 2 on day 1 followed by ifosfamide 5 g/m 2 administered as 24-h infusion, and the recommended phase II doses were docetaxel 75 mg/m 2 + ifosfamide 5 g/m 2 [12]. A subsequent pharmacokinetic analysis of the regimen by the same investigators found that the sequence of drug administration did not affect the clearance and the area under the curve (AUC) of docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…A single previous phase I study has evaluated the feasibility of the docetaxel-ifosfamide combination without G-CSF in pretreated patients with a variety of advanced solid tumors. Dose-limiting toxicity was reached at docetaxel 85 mg/m 2 on day 1 followed by ifosfamide 5 g/m 2 administered as 24-h infusion and the recommended phase II doses were docetaxel 75 mg/m 2 + ifosfamide 5 g/m 2 [12]. Similarly, our group conducted a phase I-II study of the docetaxel-ifosfamide combination with G-CSF support in patients with pre-treated metastatic breast cancer and defined an optimal dose of docetaxel 100 mg/m 2 (on day 1) and ifosfamide 5 g/m 2 (divided over days [1][2].…”
mentioning
confidence: 99%